Unraveling the Genetic Basis of Fertility Restoration for Cytoplasmic Male Sterile Line WNJ01A Originated From Brassica juncea in Brassica napus - Yang, Qian; Nong, Xiaoyi; Xu, Jize; Huang, Fan; Wang, Fang; Wu, Jiangsheng; Zhang, Chunyu; Liu, Chao (Frontiers in Plant Science, 2021)
Crosses that lead to heterosis have been widely used in the rapeseed (Brassica napus L.) industry. Cytoplasmic male sterility (CMS)/restorer-of-fertility (Rf) systems represent one of the most useful tools for rapeseed production. Several CMS types and their restorer lines have been identified in rapeseed, but there are few studies on the mechanisms underlying fertility restoration. Here, we performed morphological observation, map-based cloning, and transcriptomic analysis of the F2 population developed by crossing the CMS line WNJ01A with its restorer line Hui01. Paraffin-embedded sections showed that the sporogenous cell stage was the critical pollen degeneration period, with major sporogenous cells displaying loose and irregular arrangement in sterile anthers. Most mitochondrial electron transport chain (mtETC) complex genes were upregulated in fertile compared to sterile buds. Using bulked segregant analysis (BSA)-seq to analyze mixed DNA pools from sterile and fertile F2 buds, respectively, we identified a 6.25-Mb candidate interval where Rfw is located. Using map-based cloning experiments combined with bacterial artificial chromosome (BAC) clone sequencing, the candidate interval was reduced to 99.75 kb and two pentatricopeptide repeat (PPR) genes were found in this interval. Transcriptome sequencing showed that there were 1679 DEGs (1023 upregulated and 656 downregulated) in fertile compared to sterile F2 buds. The upregulated DEGs were enriched in the Kyoto Encyclopedia of Genes and Genomes (KEGG) lysine degradation pathway and phenylalanine metabolism, and the downregulated DEGs were enriched in cutin, suberine, and wax biosynthesis. Furthermore, 44 DEGs were involved in pollen and anther development, such as tapetum, microspores, and pollen wall development. All of them were upregulated except a few such as POE1 genes (which encode Pollen Ole e I allergen and extensin family proteins). There were 261 specifically expressed DEGs (9 and 252 in sterile and fertile buds, respectively). Regarding the fertile bud-specific upregulated DEGs, the ubiquitin–proteasome pathway was enriched. The top four hub genes in the protein–protein interaction network (BnaA09g56400D, BnaA10g18210D, BnaA10g18220D, and BnaC09g41740D) encode RAD23d proteins, which deliver ubiquitinated substrates to the 26S proteasome. These findings provide evidence on the pathways regulated by Rfw and improve our understanding of fertility restoration.